ORGANIZATIONAL CITIZENSHIP BEHAVIOR TOWARD ORGANIZATION EFFECTIVENESS: An Employee Perspective - Setiawan, Hendra; Sulistyowati, Liliek Nur; Sari, Siska Diana (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to examine the effect of organizational citizenship behavior (OCB) on organizational effectiveness based on the employee's perspective. The study took a sample of 30 (thirty)employees of BPJS Employment in Madiun City. Determination of the number of samples based on the Central Limit Theorem approach. The analytical technique used to answer the research objectives is a simple linear regression analysis model. The conclusion obtained from the research is that organizational citizenship behavior (OCB) has a positive and significant effect on organizational effectiveness. OCB has an effect on organizational effectiveness by 78.9%.